Post oil subsidy regime: entrepreneurship skills acquisition programme for youth empowerment in North Central Nigeria - Nabara, Isah Shehu; Kaduna, Abel Okoh; Mohammed Gbodo, Isah; Man, Norsida (International Organization of Scientific Research, 2024)
Post-oil subsidy regime: entrepreneurship skills acquisition program for youth empowerment in north-central Nigeria. Survey research using the Multi-Stage Cluster Sampling approach. 352 respondents were drawn from 3 selected higher institutions in 3 north-central states: Nasarawa State University-Keffi, Niger State College of Education Minna, and Kwara State University Malete.A well-structured validated questionnaire was used. Descriptive and inferential statistics were used for the analysis.The result revealed the overall mean score of 3.14 of the twenty entrepreneurship skills needed by the respondents. The overall mean score of 3.12 of the five items was agreed the overall mean score of 3.12 of the twelve attitudinal statements listed as agreed. The cluster mean score of 3.05 shows serious challenges to skill acquisition. Attitude had the highest Beta value (β=0.785, P<0.05), and awareness (β=0.199, P<0.05). The findings supported the formulated hypothesis and rejected H0. Challenges had a low Beta value of (β=0.06, P=0.23) and failed to reject H0. However, attitude and awareness had a serious impact on the entrepreneurship skills acquisition program. Hence, Adj.R2 of 50.4% is an indication of 49.6% unexplained factors not considered. The study suggests a comprehensive effort to be employed for a skills acquisition program aimed at youth development